2015
DOI: 10.15314/tjse.2015112540
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of depression levels of elite wrestling and taekwondo athletes

Abstract: The aim of this study was to compare depression levels of elite wrestling and taekwondo athletes. To the study, 130 elite wrestlers and 130 elite taekwondo athletes who were now competing in the league between Universities. "Beck Depression Inventory" was used as a tool for collecting data. According to the scale consists of 21 questions used to determine the severity of the depressive symptoms, the reliability and validity coefficient values was found to be 86. The statistical analysis of the data, the freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…To our knowledge, this was the first approach to investigate the impact of a modified MBSR program on both psychological and physiological dimensions among male wrestlers (for adult female athletes, see [15]); and 4. The focus on wrestlers appears to be particularly important, as wrestlers appeared to be at a higher risk for symptoms of depression compared to athletes of other sport disciplines [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this was the first approach to investigate the impact of a modified MBSR program on both psychological and physiological dimensions among male wrestlers (for adult female athletes, see [15]); and 4. The focus on wrestlers appears to be particularly important, as wrestlers appeared to be at a higher risk for symptoms of depression compared to athletes of other sport disciplines [7].…”
Section: Discussionmentioning
confidence: 99%
“…However, symptoms of depression may negatively impact an athlete's performance [5,6]. Kumartasli et al [7] showed that wrestlers reported higher scores for depression than taekwondo athletes. Therefore, stress and depression are two psychological variables that deserve more attention [8].…”
Section: Introductionmentioning
confidence: 99%